Childhood outcome analysis highlights risks of cannabis use in pregnancy. Issue 19 (14th May 2021) - Enos, Gary
Abstract : An analysis of results from the Adolescent Brain and Cognitive Development (ABCD) Study has added to the evidence base suggesting that the risks associated with marijuana use during pregnancy outweigh any potential benefits. However, it remains clear that amid the changing public perceptions about marijuana safety, many women who are pregnant or planning pregnancy are still likely to hear little or nothing about potential risks of use from their health care providers.